2013
DOI: 10.7150/ijms.6531
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dose of Prophylactic Dexmedetomidine for Preventing Postoperative Shivering

Abstract: Objective The aim of this study was to investigate the optimum dosage of dexmedetomidine for prevention of postanesthetic shivering.Methods One-hundred thirty two ASA physical status I-II patients scheduled for elective laparoscopic total hysterectomy were enrolled in this randomised, placebo-controlled study. Patients were randomly allocated to receive dexmedetomidine in four groups: group S (0.9% normal saline), group D0.5 (dexmedetomidine 0.5 µg/kg), group D0.75 (dexmedetomidine 0.75 µg/kg), group D1.0 (dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…50 Several elements for the clinical use of dexmedetomidine should be considered. Kim et al 19 recommended the minimum effective dose of 0.75 lgÁkg -1 for adults. Furthermore, Bozgeyik et al 24 did not find any difference between 0.5 lgÁkg -1 dexmedetomidine and placebo; however, this investigation was hampered by a relatively small sample size (30 patients per group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Several elements for the clinical use of dexmedetomidine should be considered. Kim et al 19 recommended the minimum effective dose of 0.75 lgÁkg -1 for adults. Furthermore, Bozgeyik et al 24 did not find any difference between 0.5 lgÁkg -1 dexmedetomidine and placebo; however, this investigation was hampered by a relatively small sample size (30 patients per group).…”
Section: Discussionmentioning
confidence: 99%
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Moreover, robust data on safety of use of IV dexmedetomidine in parturients is largely lacking. Callaway et al reported a decreased incidence of shivering with use of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of dexmedetomidine with opioids had better analgesia, less nausea and vomiting, less pruritus and less gastrointestinal impairment than opioids alone [54]. It abolishes post-operative shivering [55]. It is therefore essential to keep the patient warm intraoperatively because the patient tachycardia and hypertension on emergence and this helps to reduce complications like myocardial ischemia and subdural hematoma.…”
Section: Gastrointestinal Actionsmentioning
confidence: 99%